FAKTOR YANG MEMPENGARUHI KEJADIAN KEKURANGAN ENERGI KRONIS (KEK) PADA IBU HAMIL DI DESA SUKAJAYA LEMPASING KECAMATAN TELUK PANDAN KABUPATEN PESAWARAN TAHUN 2020 - Fitri Hidayati; Psiari Kusuma Wardani (Universitas Aisyah Pringsewu, 2022)
The prevalence of chronic energy deficiency (CED) in pregnant women in Lampung Province shows a fairly high number of 21.3%. This study aims to determine the factors that influence the incidence of CED in pregnant women in Sukajaya Lempasing Village, Teluk Pandan District, Pesawaran Regency in 2020. This study is a quantitative study, with a case sample of 43 pregnant women who experienced CED and a sample of 86 pregnant women who did not experience CED. This research is a correlation study with a case control approach. Data collection tools in the form of a check list sheet with Chi Square statistical test analysis technique. In the statistical test, the proportion of pregnant women who experienced CED was 43 (33.3%), pregnant women with low family income 30 (69.8%), pregnant women with risk parity 28 (65.1%), and pregnant women with a distance pregnancies at risk of 30 (69.8%). The results of the study showed that there was a relationship between low family income and the incidence of CED in pregnant women (p-value = 0.000), there was relationship between a parity with risk and the incidence of CED in pregnant women (p-value = 0.000), there was relationship between a distance pregnancies with risk and the incidence of CED in pregnant women ( p value = 0.000). The results of this study are expected to be input for Sukajaya Lempasing Village, Teluk Pandan District, Pesawaran Regency regarding prevention and treatment of pregnant women so that they can reduce the incidence of chronic energy deficiency.